Numerical modeling of changes in the bottom relief of the reservoir in the presence of gravitational waves - Sukhinov, Aleksandr Ivanovich; Kholodkov, Valentin Vladimirovich; Protsenko, Elena Anatol’yevna; Protsenko, Sof’ya Vladimirovna; Panasenko, Natal’ya Dmitriyevna (Computational Continuum Mechanics, 2023)
The issues concerning the construction of precision mathematical models of hydrodynamics of wave processes and relief formation and their adaptation to variable climatic conditions and geographical features are discussed. The incompleteness of initial information is characteristic of the new problems considered in the paper, and this difficulty is overcome by using the remote sensing and cadastral survey data. The complex of algorithms created by the authors includes raster models of a dynamically changing bottom relief that are based on the results of cadastral surveys, remote sensing data and numerical simulation results. The mathematical model of transport of bottom materials makes it possible to predict the bottom relief dynamics due to the movement of water and multicomponent solid particles and to take into account soil porosity, critical shear stress values at which sediment movement begins, turbulent exchange, bottom geometry transformation, wind currents, and bottom friction. The programs developed on the basis of a set of algorithms are used to perform predictive calculations of the processes of coastal erosion and reconstruction of the bottom relief. Using the programs, the complex geometry of the reservoir bottom is represented by a raster model that takes into account the data of cadastral surveys and remote sensing, the type and characteristics of the source of water fluctuations, and the direction and speed of wind. When analyzing the state of a water body as a whole, the characteristic features of natural processes, in particular, the spatial and temporal variability of the bottom relief, are considered. Modeling the transport of sediments has shown that, in the course of time, they are formed near the coastal zone, which leads to a decrease in the slope of its bottom and a gradual shallowing of the reservoir.